(untitled) (PerCursos, 2022)
Since the second half of the twentieth century, with the Technical-Scientific-Informational Revolution, the production of geographic space has been increasingly characterized by the uses of science, information, consumption and finance. In Education, the teaching-learning process is marked by digital information and communication technologies (TDIC). Therefore, the teacher should not neglect the fact that TDIC are part of the student’s daily life and, thus, can be used as strategies for the amplification of learning in the wake of the student’s prominence as a protagonist of the educational process. For this, it is necessary that teachers know cyberculture and participate in it, including in their professional practice the use of TDIC, considering the availability ofinfrastructural and socioeconomic possibilities of the school and the community involved in the educational process. For the teaching-learning of Geography in Basic Education, specifically in Elementary School II, we believe that the uses of TDIC can mean methodological strategies for the understanding of contents that are fundamental to the understanding of the dynamics of geographical spacewith regard to various geographic scales. Among these contents, we highlight that of cartographic literacy, which is the learning of notions of location, organization and representation of geographical space, as a product and condition of human actions and social relations. Therefore, in this work we aim to analyze the possibilities of using the Google Earth Pro software for teaching-learning Geography in Elementary School II, especially regarding the understanding of the cartographic representation of geographic space. We conclude that, for teaching-learning Geography, this software can be an important didactic-pedagogical tool, useful for the development of a dynamic, active and contextualized educational process with regard to contents such as the (re)production of geographical space and that of cartographic language.